Why selected autoclave-cured Double–Double laminates are particular prone to warpage - Kappel, E.; Klomp, R. (Elsevier, 2026)
Double–Double (DD) laminates provide unique design and manufacturing opportunities. This makes them a promising challenger for conventional laminates used in aerospace composite parts today. DD laminates benefit from an effect denoted as ’homogenization’, which leads to a mechanical behavior known from orthotropic laminates, without complex coupling effects, although DD laminates have asymmetric ply-stacking sequences. Manufacturing aspects and particularly the topic of process-induced distortions (PID) have attracted little attention in DD context. The present article is dedicated to this topic. It outlines why some DD laminates show warpage and twist after a typical 180°C curing process, while others remain almost flat. Hence, the article provides practical guidance for selecting building-block stacking sequences, which induce minimum warpage.